Pregestational body mass index, gestational weight gain, and risks for adverse pregnancy outcomes among Taiwanese women: A retrospective cohort study - Tai-Ho Hung; T'sang-T'ang Hsieh (Elsevier, 2016)
Objective: To investigate the associations between maternal pregestational body mass index (BMI), gestational weight gain (GWG), and adverse pregnancy outcomes among Taiwanese women. Materials and Methods: A retrospective cohort study was conducted among all singletons without fetal anomalies delivered to women at Taipei Chang Gung Memorial Hospital between 2009 and 2015. Two study cohorts were selected for analysis: all deliveries after 24 0/7 weeks of gestation (Cohort 1, n=12,064) and all live births after 37 0/7 weeks of gestation excluding maternal overt diabetes mellitus and chronic hypertension (Cohort 2, n=10,973). The associations between pregestational BMI, GWG outside the 2009 Institute of Medicine (IOM) guidelines, and adverse pregnancy outcomes were assessed using multivariable logistic regression analysis. Results: In Cohort 1, the prevalence of pregestational underweight, normal weight, overweight, and obesity was 14.0%, 74.8%, 9.0%, and 2.2%, respectively. Compared with the women with normal weight, maternal underweight was associated with increased risk for placental abruption, small-for-gestational age, and low birth weight (<2500 g). In contrast, overweight and obese women were at risk for gestational diabetes mellitus, preeclampsia, dysfunctional labor, cephalopelvic disproportion, large-for-gestational age, and macrosomia (>4000 g). In Cohort 2, GWG below the IOM guidelines were associated with higher rates of gestational diabetes mellitus, small-for-gestational age, and low birth weight, while GWG above the IOM guidelines were with higher rates of primary cesarean delivery, large-for-gestational age, and macrosomia in women with pregestational underweight or normal weight. Normal weight women were more likely to have placental abruption with GWG below the guidelines and to have preeclampsia with GWG above the guidelines. For overweight and obese women, GWG below the guidelines was associated with a higher rate of gestational diabetes mellitus, but GWG above the guidelines was associated with a higher rate of macrosomia. Conclusions: Women with abnormal pregestational BMI are at risk for adverse maternal and neonatal outcomes. Moreover, GWG has a differential effect on the rates of adverse pregnancy outcomes between women of different pregestational BMI categories.